2009
DOI: 10.1159/000206149
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Perioperative Rehabilitation in Elective Conventional Resection of Colonic Cancer: Results from the German Multicenter Quality Assurance Program ‘Fast-Track Colon II’

Abstract: Aim: Multimodal perioperative rehabilitation in patients undergoing curative conventional colonic resection for cancer has not yet been studied in a multicenter setting. In 2005, a nationwide quality assurance program was initiated in Germany in an unselected patient population. Methods: The prospective multicenter data collection includes patients from 24 German hospitals. All hospitals had established ‘fast-track’ rehabilitation as the standard perioperative treatment in elective colonic resection, and all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 52 publications
2
11
0
4
Order By: Relevance
“…These programmes do not, therefore, appear to place the patient at any extra risk. Our results are similar to previous multicenter studies [27,28] in terms of surgical complications, mortality and readmission rate. The surgical complication rate was 24% compared to the 14.1% reported by Schwenk et al [27] and 20% reported by Braumann et al [28].…”
Section: Discussionsupporting
confidence: 92%
“…These programmes do not, therefore, appear to place the patient at any extra risk. Our results are similar to previous multicenter studies [27,28] in terms of surgical complications, mortality and readmission rate. The surgical complication rate was 24% compared to the 14.1% reported by Schwenk et al [27] and 20% reported by Braumann et al [28].…”
Section: Discussionsupporting
confidence: 92%
“…48 Such programs have been shown to be effective in different surgical populations. [48][49][50] It has also been suggested that rehabilitation programs should be reserved for patients who require postoperative care after the prehabilitation program. 47 If these multidisciplinary prehabilitation and rehabilitation programs are implemented, anesthesiologists should play a prominent role in their management.…”
Section: Future Considerationsmentioning
confidence: 99%
“…Despite its convincing results, world-wide adoption for various elements of Fast Track surgery is poor [42]. Still, in a recent report from a German quality assurance program (Fast Track Colon II), compliance for epidural anaesthesia (89%), systemic basic non-opoid analgesia (93%), intraoperative fluid restriction (81%), early oral feeding (73%) and enforced mobilization (84%) was high in a multicenter setting [43].…”
Section: Perioperative Managementmentioning
confidence: 99%